PENDIDIKAN BERBASIS MULTIKULTURAL PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MEMBANGUN KERJASAMA - Harun Harun; Nurlaili Nurlaili; Alimni Alimni (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2023)
This study aims to describe and analyze how the planning, implementation, supporting factors and inhibiting factors and evaluation of multicultural-based education. This type of research is descriptive qualitative research. Data collection techniques using observation, interviews, and documentation. The results of this study indicate: 1) Planning in multicultural-based education to create peaceful cooperation